Adsorption of flupyradifurone onto soils: kinetics, isotherms, and influencing factors. Issue 12 (29th November 2022) - Fang, Nan; Luo, Yuqin; Jiang, Jinhua; Lu, Zhou; Hou, Zhiguang; Zhao, Xueping; Wang, Xiangyun; Tang, Tao; Zhang, Changpeng; Lu, Zhongbin
Abstract : The new pesticide flupyradifurone is highly mobile in soil and poses a potential risk to water environments. Abstract : The study of the adsorption properties of pesticides in soil is essential to assessing the risk of their pollution of nearby aquatic environments. To reveal the adsorption mechanisms of flupyradifurone (FPO) on soil, batch experiments in five different soils were carried out in this study. The adsorption kinetics and isotherms of FPO in five soils were well fitted by using several models ( R 2 = 0.922–0.998). It was found that both physical and chemical adsorption were included in the adsorption process of FPO in soils; the monolayer adsorption of FPO occurred with a non-uniform energy distribution on the soil surface, and the internal particle diffusion was not the only rate-controlling step. The adsorption coefficients calculated by using the Langmuir ( K L ) and Freundlich ( K F ) models were 0.0158–0.0982 and 1.053–9.798, respectively. In addition, the main factors affecting the adsorption of FPO in soil were investigated by stepwise regression fitted with the adsorption coefficient ( K d ) and the soil properties. It was found that the organic carbon content was the main factor ( R 2 = 0.857, p < 0.05). Therefore, the organic carbon adsorption coefficients ( K oc ) were calculated. The results (1.0532–5.6529) indicated that FPO has a low affinity and high mobility in the soils, and may cause water environment pollution around the soil. Therefore, FPO should be used cautiously in paddy fields. These research findings were important for elucidating the sorption behaviour and transport of FPO in soil.